1995
DOI: 10.1111/j.1472-8206.1995.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell activation involves plasma membrane potential‐ and thapsigargin‐sensitive intracellular calcium pools

Abstract: The regulation and role of the intracellular Ca2+ pools were studied in rat peritoneal mast cells. Cytosolic free calcium concentration ([Ca2+]i) was monitored in fura-2 loaded mast cells. In the presence of Ca2+ and K+, compound 48/80 induced a biphasic increase in [Ca2+]i composed of a fast transient phase and an apparent sustained phase. The sustained phase was partially inhibited by the addition of Mn2+. DTPA, a cell-impermeant chelator of Mn2+, reversed this inhibition, suggesting that a quenching of fura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…This observation is in line with previous results dealing with the secretory effect induced by the synthetic polyamines methoctramine and compound 48/80 or by cationic peptides (Church et al 1991;Kassel et al 1995;. In contrast, Purcell et al (1996) indicated that the secretory effect of spermine, but not that of compound 48/80, was dependent upon extracellular calcium, but results were not shown and the method used was not indicated.…”
Section: Discussionsupporting
confidence: 90%
“…This observation is in line with previous results dealing with the secretory effect induced by the synthetic polyamines methoctramine and compound 48/80 or by cationic peptides (Church et al 1991;Kassel et al 1995;. In contrast, Purcell et al (1996) indicated that the secretory effect of spermine, but not that of compound 48/80, was dependent upon extracellular calcium, but results were not shown and the method used was not indicated.…”
Section: Discussionsupporting
confidence: 90%
“…6A). Since lipid rafts are also involved in the exocytotic process [48], a potential inhibitory effect of MbCD on secretory granule fusion with the plasma membrane was assessed by pretreating cells with MbCD prior to stimulation with the Ca 2+ ionophore A23187 [34]. No significant inhibition of A23187-induced exocytosis was found after pretreatment with MbCD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular calcium was measured from Fura-2-loaded mast cell suspensions using a spectrofluorimeter (Hitachi F-2000) essentially as previously described [34]. Briefly, mast cells (110 6 cells/ml) were incubated with 1 mM Fura-2/AM for 15 min at room temperature in HEPES buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular calcium was measured from Fura-2-loaded astrocytoma cell suspensions using a spectrofluorimeter (Hitachi F-2000) essentially as previously described (Kassel et al, 1995;Lynch et al, 1994). Briefly, astrocytoma cells (1 3 10 6 cells/mL) were incubated with 1 lM Fura-2/AM for 45 min at room temperature in HEPES buffer (137 mM NaCl, 2.7 mM KCl, 0.3 mM CaCl 2 , 1.0 mM MgCl 2 , 0.4 mM NaH 2 PO 4 , 5.6 mM glucose, 10 mM HEPES, and NaOH to pH 7.4).…”
Section: Measurement Of Intracellular Calciummentioning
confidence: 99%